A comparative bacteriological profile and antibiogram of dacryocystitis - Shah, CP; Santani, D (Nepalese Journal of Ophthalmology, 2011)
Introduction: Dacryocystitis is an infection and an inflammation of the lacrimal sac and is an important cause of ocular morbidity in India. Objective: To isolate and identify the bacterial patterns associated with dacryocystitis and to determine their antibacterial sensitivity pattern. Materials and methods: A total of 100 lacrimal swab materials were subjected to bacaterial analysis. Children less than 8 years were not included in the study. Results: The chances of chronic dacryocystitis were more than acute dacryocystitis and were commonly found in the age group of 41 - 50 years. Females were more vulnerable to the infection than males. From a 100 samples a total of 122 bacterial isolates were obtained. Both Gram positive and Gram negative bacteria were equally distributed in the study. The most common organism associated with the infection was S. aureus. The antibacterial sensitivity showed more effectiveness towards Gram positive isolates than Gram negative isolates. Conclusion: Both Gram positive and Gram negative organism are associated with with chronic dacryocystitis. Knowledge of the bacteriology of dacryocystitis and the susceptibility of the bacteria towards antibiotics will better guide a clinician in the choice of the medication for the most appropriate drug for the treatment. Keywords: Acute dacryocystitis, chronic dacryocystitis, lacrimal sac, nasolacrimal duct DOI: http://dx.doi.org/10.3126/nepjoph.v3i2.5265 Nepal J Ophthalmol 2011; 3(2): 134-139